Surface modification of polymethyl-methacrylate using atmospheric pressure argon plasma jets to improve surface flashover performance in vacuum - Shao, Tao; Zhou, Yixiao; Zhang, Cheng; Yang, Wenjin; Niu, Zheng; Ren, Chengyan (IEEE transactions on dielectrics and electrical insulation, 2015)
Hydrophilic modification of polymethyl methacrylate (PMMA) surface is performed by atmospheric pressure plasma jet (APPJ) in Ar gas for improving the PMMA surface flashover performance in vacuum. In the experiments, APPJ is driven by a microsecond-duration pulsed generator, which has voltages of 0-30 kV, a rise time of 300 ns and a full width at half maximum of 2μs. Characteristics of the APPJ are analyzed according to its voltage and current waveform, discharge image and optical emission spectrum. Furthermore, surface properties of the PMMA surface before and after the treatment are characterized by water contact angle measurements and morphology observations. Results show that the main species of the plasma jet are composed of N 2 , Ar, OH, and O, among which such polar groups as OH and O enhance the hydrophilic property of the PMMA surface. The water contact angle decreases from 68° to a minimum value (16°) after the treatment. In addition, all the surface flashover voltages in vacuum for the PMMA samples treated by APPJ are higher than those for the untreated PMMA samples.